COMPARISON OF MINI CHOLECYSTECTOMY VERSUS OPEN CHOLECYSTECTOMY IN PATIENTS WITH CHOLELITHIASIS - Uzair Karim Qasrani; Muhammad Faizan; Zarnab Siddique; Muhammad Khalid (Journal of University Medical & Dental College, 2020)
BACKGROUND & OBJECTIVES: The goal of this study is to compare the results of mini cholecystectomy with open conventional cholecystectomy in the management of cholelithiasis. METHODOLOGY: A total of 100 cases; 50 cases in each group was included in the study. 100 patients were admitted from OPD of Teaching Hospital Dera Ghazi Khan fulfilling inclusion criteria. Demographic information was recorded. All admitted patients were diagnosed after taking history and performing clinical examination. Written consent was obtained. Statistical data input and scrutiny done with the help of SPSS 11. All the Information was inspected by the proposed investigation plan. RESULTS: Mean age of all patients was 39.96±3.84 years. Age range of patients was 30-48 years. In Group-A (Mini Cholecystectomy Patients) mean hospital stay was 5.38±1.15 and in Group-B (Conventional Cholecystectomy Patients) mean hospital stay was 3.02±0.58 days respectively. At 1st visit 14(28%) patients in Group-B and only 1(2%) patient in Group-A had wound infection. According to p-value wound infection was significantly correlated with treatment group. Patients in Group-A had less infection rate in comparison to Group-B patients. i.e. (p-value=0.000) whereas at 2nd visit 8(16%) patients in Group-B and 3 patients in Group-A suffered from wound infection. At 2nd visit wound infection was statistically same in both treatment groups. i.e. (p-value=0.110). It was observed that in Group-B 44(88%) of the patients had severe pain whereas only 12(24%) of the patients in Group-A had severe pain. Keeping in mind this results rate of severe pain at 12th hour was high in Group-B patients in contrast to Group-A patients. i.e. (p-value=0.000). CONCLUSION: Mini cholecystectomy is effective and related with less patient’s uneasiness in terms of post-operative pain and infection as well as with less hospital stay.